2017
DOI: 10.1038/cddis.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-induced LRG1 promotes angiogenesis and mesenchymal stem cell migration in the subchondral bone during osteoarthritis

Abstract: The incomplete understanding of aberrant neovascularization, which contributes to osteoarthritis suggests that additional modulators have yet to be identified. Our objective was to identify the role of Leucine-rich-alpha-2-glycoprotein1 (LRG1), a new regulator of pathogenic angiogenesis, in osteoarthritis progression and to develop effective treatment strategies. In this study, immunohistochemistry showed that LRG1 was increased in the subchondral bone and articular cartilage in anterior cruciate ligament tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
106
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 44 publications
7
106
0
3
Order By: Relevance
“…A recent study also showed that TNF-a induces LRG1 expression to promote angiogenesis and mesenchymal stem cell migration in the subchondral bone of osteoarthritis joints. 53 In silico analysis of LRG1 promoter indeed indicated multiple potential binding sites for p65 NF-kB and STAT3 transcription factors. Thus, it is plausible that the inflammatory cytokines known to be involved in the progression of DKD, such as TNF-a and IL-6, 54 may also participate in LRG1 upregulation in diabetic kidneys.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study also showed that TNF-a induces LRG1 expression to promote angiogenesis and mesenchymal stem cell migration in the subchondral bone of osteoarthritis joints. 53 In silico analysis of LRG1 promoter indeed indicated multiple potential binding sites for p65 NF-kB and STAT3 transcription factors. Thus, it is plausible that the inflammatory cytokines known to be involved in the progression of DKD, such as TNF-a and IL-6, 54 may also participate in LRG1 upregulation in diabetic kidneys.…”
Section: Discussionmentioning
confidence: 98%
“…Wang, Xu et al, 2017). It can significantly attenuate the severity of arthritis and joint damage by significantly reducing the production of serum anti-complement II (CII), tumor necrosis factor alpha (TNF-α), IL-1β, and IL-6 (Li, Tan, Wang, & Li, 2017;Y. Wang, Xu et al, 2017).…”
mentioning
confidence: 99%
“…In murine hippocampal HT22 cells, it was found that AP induced the expression and translocation of Nrf2 from the cytoplasm to the nucleus, thereby activating ARE gene transcription and heme oxygenase (HO-1) expression (Y. Wang, Xu et al, 2017). These findings led to an assertion that AP attenuates the progression of OA through its potential antioxidant effects by regulating the Keap1-Nrf2-ARE signaling pathway.…”
mentioning
confidence: 99%
“…In the present study, PRP increased plasma levels of TNFα, which might induce angiogenesis because of its mutual interaction with platelet‐activating factor present in PRP (Montrucchio et al, ), or due to the induction of mediators like LRG1 that promotes angiogenesis and mesenchymal stem cell migration (Wang et al, ). In addition, PRP also increased GRO‐α.…”
Section: Discussionmentioning
confidence: 72%